Restoring Integrity: Re-Voting of the 2025 Serang Regent Election and Its Transformative Power for Local Democracy - Maulana, Muhammad Akbar; Nurfaisal, Muhammad Dwi; Al-Ra’zie, Zakaria Habib (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2025)
Re-Voting in the Regional Head Election is one of the corrective instruments in the Indonesian electoral democracy system which aims to ensure fairness and integrity in the implementation of elections. This study specifically examines the implementation of Re-Voting in the context of the 2025 Serang Regency Regent Election, which was decided by the Constitutional Court as a result of proven violations of the principle of neutrality by a number of village heads who actively provided support to one of the candidate pairs. This study aims to analyze the juridical aspects underlying Re-Voting decisions, identify administrative challenges in their implementation, and evaluate their impact on the quality of local democracy in Serang Regency. The research approach used is qualitative with a juridical-normative method, supported by secondary data analysis in the form of Constitutional Court decisions, related laws and regulations, and reliable news sources from mainstream media. The results of the study show that the implementation of Re-Voting in Serang Regency not only indicates weak supervision of village officials in local political contests, but also highlights the urgency of regulatory reform related to the neutrality of village apparatus in the Regional Elections. In addition, administrative challenges such as budget limitations and coordination between election organizing agencies are important highlights that can affect the effectiveness of Re-Voting. This study recommends strengthening mechanisms to prevent violations of neutrality, as well as increasing the institutional capacity of election organizers in dealing with complex local political dynamics.